The Effect of Tax Rates on Fiscal Evasion and Avoidance - Gashi, Mentor; Kukaj, Halil (European Journal of Sustainable Development, 2016)
Abstract: In order to findelements that destimulate fiscal evasion or avoidance, we have submitted six elements, through the questionnaire, to determine which elements are that destimulate the fiscal evasion and avoidance, and evaluate their impact.This paper is focused in customs duty avoidance.The elements that we have submitted to evaluate their power, are: Powerful control during customs clearance, more efficient post clearance control, probability of subject investigation, higher fines, lower tax rate, consciousness of companies.In this research, we collected 248 answers, and can present these results:Fiscal policy or lower tax rate is a powerful element that can't stimulate a tax evasion and/or avoidance, for this element we received 68 answers from respondentsor 27.42%. The other element is powerful control from customs during clearance, for this element we received 52 answers from respondents or 20.97%. The next element following is consciousness of companies, for this element are 36 answers from respondents or 12.90%. The next element investigation are 33 answers or 12.90%, post clearance control are 31 respondents or 12%, the last element is higher fines, that are 28 respondents or 11.29%.As presented, all the elements are very close to each other, except first and second element, which are: lower tax rate and powerful control from customs during clearance. These elements have more effect, that destimulate tax evasion and avoidance. Keywords: tax rates, fiscal evasion, fiscal avoidance, elements of destimulate.